2021
DOI: 10.1136/jitc-2021-003334
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome is associated with the clinical response to anti-PD-1 based immunotherapy in hepatobiliary cancers

Abstract: BackgroundThe gut microbiome is associated with the response to immunotherapy for different cancers. However, the impact of the gut microbiome on hepatobiliary cancers receiving immunotherapy remains unknown. This study aims to investigate the relationship between the gut microbiome and the clinical response to anti-programmed cell death protein 1 (PD-1) immunotherapy in patients with advanced hepatobiliary cancers.MethodsPatients with unresectable hepatocellular carcinoma or advanced biliary tract cancers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 55 publications
(58 reference statements)
4
134
0
Order By: Relevance
“…However, only F. prausnitzii is reproducible for all datasets included in the analysis. Identified biomarkers are confirmed by many published studies [Sivan et al, 2015; Chaput et al, 2017; Frankel et al, 2017; Gopalakrishnan et al, 2018; Matson et al, 2018; Jin et al, 2019; Peters et al, 2019; Zheng et al, 2019; Tanoe et al, 2019; Derosa et al, 2020; Coutzac et al, 2020; Limeta et al, 2020; Fedorov et al, 2020; Heshiki et al, 2020; Sun et al, 2020; Lee et al, 2021; Spencer et al, 2021; Mao et al, 2021; Usyk et al, 2021; Lee et al, 2022]. Additionally, we identified 140 KOGs as reproducible functional biomarkers of positive immunotherapy outcome corresponds to fatty acids biosynthesis, polysaccharide biosynthesis and degradation, peptidoglycan and lipopolysaccharide biosynthesis, cobalamin biosynthesis, fructoselysine/glucoselysine utilization system, sporulation, and motility/secretion system.…”
Section: Resultsmentioning
confidence: 57%
“…However, only F. prausnitzii is reproducible for all datasets included in the analysis. Identified biomarkers are confirmed by many published studies [Sivan et al, 2015; Chaput et al, 2017; Frankel et al, 2017; Gopalakrishnan et al, 2018; Matson et al, 2018; Jin et al, 2019; Peters et al, 2019; Zheng et al, 2019; Tanoe et al, 2019; Derosa et al, 2020; Coutzac et al, 2020; Limeta et al, 2020; Fedorov et al, 2020; Heshiki et al, 2020; Sun et al, 2020; Lee et al, 2021; Spencer et al, 2021; Mao et al, 2021; Usyk et al, 2021; Lee et al, 2022]. Additionally, we identified 140 KOGs as reproducible functional biomarkers of positive immunotherapy outcome corresponds to fatty acids biosynthesis, polysaccharide biosynthesis and degradation, peptidoglycan and lipopolysaccharide biosynthesis, cobalamin biosynthesis, fructoselysine/glucoselysine utilization system, sporulation, and motility/secretion system.…”
Section: Resultsmentioning
confidence: 57%
“…In hepatobiliary cancers, a higher abundance of Ruminococcus callidus and Erysipelotrichaceae bacterium-GAM147 was found in patients with longer progression-free survival (PFS), while a higher abundance of Veillonellaceae was found in patients with shorter PFS and overall survival (OS). The gut microbiome is associated with the clinical response to anti-programmed cell death protein 1 (PD-1) therapy in patients with hepatobiliary cancers [ 42 ]. In metastatic melanoma, Faecalibacterium enrichment is associated with a good clinical response to ipilimumab (an immune checkpoint inhibitor targeting CTLA-4) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In hepatobiliary cancers, the gut microbiome is related to the response to PD-1 inhibitor treatment. Functional annotation indicated that the taxa enriched in the clinical benefit response group were associated with energy metabolism, whereas those in the non-clinical benefit group were associated with amino acid metabolism, which may modulate the clinical response to immunotherapy [ 42 ]. This indicates that the gut microbiota might regulate host immunity by influencing the metabolism in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The favorable clinical outcome during anti-PD1 therapy was linked to the presence of Akkermansia muciniphila , as well as to high diversity and abundance of Clostridiales/Ruminococcaceae / Faecalibacterium, Bifidobacterium longum , Collinsella aerofaciens , and Enterococcus faecium . Conversely, the poor responders harbored a low diversity and high abundance of Bacteroidales ( Robert et al, 2011 ; Sivan et al, 2015 ; Gopalakrishnan et al, 2018 ; Mao et al, 2021 ; Wong et al, 2021 ; Sevcikova et al, 2022 ).…”
Section: Gut Microbiota–antibiotics–antitumoral Agents Trialoguementioning
confidence: 99%